Using Tablet Devices and Social Media in a Course about the 2012 US Election Campaign. Issue 1 (31st December 2014) - Brewer, Paul R.; Begleiter, Ralph J.; Anderson, Katherine; Isaacs, Meredith
ABSTRACT: The use of both tablet devices and social media is increasingly popular among the American public. With this in mind, this article discusses our use of the technologies in a course about the 2012 US election campaign. We provided all students in our course with an iPad, created a private Facebook group, and devised a variety of approaches for integrating the technologies into the course. Surveys at the beginning and the end of the course showed that students frequently used their iPad for political and instructional purposes and that their self-confidence in using tablet devices, apps, and social media for political purposes increased during the semester. Open-ended responses and our own observations also suggest that use of the technologies fostered active online conversations about course material. In particular, use of the iPad and the Facebook group in combination during in-class video screenings, guest speakers, and debates facilitated lively, creative interactions among students and between students and instructors.